Analysis of Leading Sectors in Driving the Economy of Majene Regency - Marsida, Marsida (AIBPM Publisher, 2023)
West Sulawesi is the province with the lowest unemployment rate in Indonesia. Majene is a regency in West Sulawesi with increasing economic growth. This research aims to analyze the typology and leading sectors in Majene Regency. This research uses the LQ, Shift Share, and Klassen Typology analysis methods. The data used is secondary data in the form of GRDP of Majene Regency and West Sulawesi Province for 2018-2022 which is sourced from the Central Statistics Agency (BPS). The analysis is carried out by determining the base sector, then determining the progressive sector, and finally formulating a sector typology using the Klassen Typology. The research results show that those included in the leading sectors are the mining sector, electricity and gas procurement, transportation, accommodation provision, information, financial services, real estate, government administration, educational services and other services. This sector has the potential to be developed and it is hoped that the results of this research can become the basis for an economic development strategy by looking at the potential of each sector typology.